(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the article has analyzed Ahmad Yugnakiy’s «Hibbat ul-haqqayiq» works and determined their role in the history of oratory and art of speech, including giving them a scientific-theoretical assessment.